2019
DOI: 10.1115/1.4043517
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Flat Plate Solar Air Heater Integrated With an Array of Pin Fins on Absorber Plate for Enhancement in Thermal Performance

Abstract: This paper presents a three-dimensional numerical analysis of a flat plate solar air heater in the presence of a pin fin array using the computational fluid dynamics (CFD) software tool ansys fluent 16.2. The effect of geometric parameters of pin fins as well as the flow Reynolds number (4000–24,000) on the effective efficiency is evaluated. The longitudinal pitch (PL) of pin fin array is varied as 30 mm, 40 mm, and 50 mm and the diameter (Dw) is varied as 1.0 mm, 1.6 mm, and 2.2 mm. The results show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The obtained simulations get significant results. As an example of a simple rectangular mold section, it was found that the applied visualization technique allows us to observe the filling process in the mold cavity in good agreement with the experimental and simulation results (Manjunath, Vasudeva Karanth, & Yagnesh Sharma, 2019) Injection molded components are consistently designed to minimize the design and creation of information content of enterprise systems. However, the resulting designs are very complex and often exhibit relationships between various quality attributes.…”
Section: Introductionmentioning
confidence: 52%
“…The obtained simulations get significant results. As an example of a simple rectangular mold section, it was found that the applied visualization technique allows us to observe the filling process in the mold cavity in good agreement with the experimental and simulation results (Manjunath, Vasudeva Karanth, & Yagnesh Sharma, 2019) Injection molded components are consistently designed to minimize the design and creation of information content of enterprise systems. However, the resulting designs are very complex and often exhibit relationships between various quality attributes.…”
Section: Introductionmentioning
confidence: 52%
“…It found that increasing the number of partitions to the glazing wall leads to a decrease significantly in the value of average Nusselt, and therefore minimization of heat loss to the outside of flat solar thermal collector. Manjunath et al (2019) evaluated the effect of pin fin array on the instantaneous thermal and effective efficiency of flat plate solar air heater using three dimensional CFD analysis for different flow rate conditions, as well as the influence of fin diameter and longitudinal pitch on the effective efficiency will be brought out. They found that larger fin diameter and lower pitch distances of pin fin produce a relatively higher instantaneous thermal efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement of thermal performance of a partially covered photovoltaic wavy plate was 11.21% over the plain plate. Manjunath et al 26 mathematically investigated the SAH with an array of pin fins based on absorber plates. The longitudinal pitch differed from 30 to 50 mm, distances across pin fins fluctuated from 1 to 2.2 mm, and Re reaches from 4000 to 24,000.…”
Section: Introductionmentioning
confidence: 99%